2021
DOI: 10.3390/en14196309
|View full text |Cite
|
Sign up to set email alerts
|

Edge Computing and IoT Analytics for Agile Optimization in Intelligent Transportation Systems

Abstract: With the emergence of fog and edge computing, new possibilities arise regarding the data-driven management of citizens’ mobility in smart cities. Internet of Things (IoT) analytics refers to the use of these technologies, data, and analytical models to describe the current status of the city traffic, to predict its evolution over the coming hours, and to make decisions that increase the efficiency of the transportation system. It involves many challenges such as how to deal and manage real and huge amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…At the end of their study, they propose an agile optimization approach to handle the current raised problems and converge to sustainable smart cities. In another work, Peyman et al [48] review the state-of-the-art of IoT in intelligent transportation systems and identify challenges posed by cloud, fog, and edge computing in ITS. They develop a methodology based on agile optimization algorithms for solving a dynamic ridesharing problem (DRSP) in the context of edge/fog computing.…”
Section: Sustainability and Smart Urban Mobilitymentioning
confidence: 99%
“…At the end of their study, they propose an agile optimization approach to handle the current raised problems and converge to sustainable smart cities. In another work, Peyman et al [48] review the state-of-the-art of IoT in intelligent transportation systems and identify challenges posed by cloud, fog, and edge computing in ITS. They develop a methodology based on agile optimization algorithms for solving a dynamic ridesharing problem (DRSP) in the context of edge/fog computing.…”
Section: Sustainability and Smart Urban Mobilitymentioning
confidence: 99%
“…It was shown that this approach outperformed the solutions provided by its original version. Similarly, Peyman et al [77] provided a comprehensive review of the state of the art of the Internet of Things in intelligent transportation systems (ITSs). In this context, challenges were identified for cloud computing, fog computing, and edge computing.…”
Section: Evolutionarymentioning
confidence: 99%
“…The integration of IoT into EVCS marks a transformative step in the evolution of smart transportation infrastructure [5]. This fusion introduces a level of sophistication and efficiency previously unattainable in traditional EVCS.…”
Section: Introduction To Iot In Vehicle Charging Stationsmentioning
confidence: 99%
“…Comprehensive Performance Analysis: Our model outperforms existing IDS solutions in accuracy and resilience, proven through extensive testing. 5.…”
mentioning
confidence: 99%